OUTCOMES OF PEDIATRIC SUPRACONDYLAR HUMERUS FRACTURE TREATMENT BY CLOSED REDUCTION AND PERCUTANEOUS KIRSCHNER WIRE FIXATION IN THAI NGUYEN NATIONAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: This study aims to evaluate outcomes and analyze factors affecting the results of closed reduction and percutaneous kirschner wire fixation in pediatric supracondylar humeral fractures.Subjects and methods: This cross-sectional study was conducted on 35 cases of closed supracondylar humerus fractures in children were treated with closed reduction and percutaneous kirschner wire at the Department of Pediatric Surgery in Thai Nguyen National Hospital, from July 2024 to April 2025.Results: All 35 patients achieved clinical carrying angle and demonstrated good rehabilitation. No cases of radial or ulnar nerve injury were observed in our study.Conclusion: The lateral-pin technique under fluoroscopic guidance is an effective option for the treatment of supracondylar humeral fractures in children. This technique provides good functional and cosmetic outcomes while minimizing the risk of iatrogenic ulnar nerve injury.
Keywords: Closed supracondylar fracture, good rehabilitation, ulnar nerve injury.